PENGEMBANGAN SISTEM DIGITALISASI ARSIP SURAT DI LINGKUNGAN PUSAT KEUANGAN MABES POLRI SELONG BEBASIS WEBSITE: Archiving System, Data Security, Document Digitization, Waterfall, Website - Buani, Duwi Cahya Putri; Johansyah, Septian Dwi Nur (JURNAL AKADEMIKA, 2025)
The conventional letter archiving system still employed by government institutions such as the Financial Center of the National Police Headquarters (Mabes Polri) Selong faces several limitations, including document loss risks, slow retrieval processes, and restricted physical storage capacity. To address these issues, this study developed a web-based letter archiving system using the Waterfall development model. The system was designed to replace manual processes with a more structured, accurate, and efficient digital workflow. Key features of the system include account registration, login authentication, document management, category and file management, user administration, and theme customization. System testing demonstrated that all eight core features operated successfully. Performance evaluation using GTmetrix achieved a 90% performance score with an average page load time of 2.2 seconds. Security testing confirmed that the system is free from malware and blacklist threats, with only two medium-level risks identified out of forty test cases. The results indicate that the proposed system effectively enhances administrative efficiency and provides a reliable digital archiving solution to support correspondence management within government institutions.